Clinical and Management Dilemmas Concerning Early-Stage Cervical Cancer in Pregnancy – A Case Report - Kurniadi A; Setiawan D; Kireina J; Suardi D; Salima S; Erfiandi F; Andarini MY (Dove Medical Press, 2023)
Andi Kurniadi,1 Dani Setiawan,1 Jessica Kireina,1 Dodi Suardi,1 Siti Salima,1 Febia Erfiandi,1 Mia Yasmina Andarini2 1Department of Obstetrics and Gynecology, Universitas Padjadjaran, Bandung, Indonesia; 2Faculty of Medicine, Universitas Islam Bandung, Bandung, IndonesiaCorrespondence: Andi Kurniadi, Department of Obstetrics and Gynecology, Universitas Padjadjaran, Bandung, Indonesia, Tel +62 812 2028 6197, Email andi.kurniadi@unpad.ac.idBackground: Cervical cancer in pregnancy is rare and its management remains a formidable challenge. Clinical upstaging is a serious concern. Presentation may mimic pregnancy-related conditions, thus delaying diagnosis and leading to an advanced stage at presentation. In addition, concerns regarding chemotherapy safety in pregnancy may hinder its administration. Definitive therapy may also be delayed due to pregnancy.Case Report: A 37-year-old G3P2A0 10- 11 weeks pregnant woman was diagnosed with stage IB2 cervical cancer. We originally planned to perform neoadjuvant chemotherapy with paclitaxel 175mg/m2 and carboplatin 6 AUC every 21 days followed by caesarean section and radical hysterectomy. However, preoperatively, the tumor had grown further and progressed to stage IIB. Postpartum radiotherapy was thus indicated. Lower segmental caesarean section along with bilateral salpingectomy and ovarian transposition were performed. Radiotherapy was administered through external beam radiation therapy and brachytherapy. The patient delivered a small for gestational age male baby with no abnormalities. At 2-month follow-up, the infant appeared generally healthy.Conclusion: Cancer diagnosis during pregnancy adversely impacts women's physical and psychological states. Symptoms may mimic pregnancy-related conditions, thus delaying diagnosis. Its management involves a multidisciplinary team to protect both maternal and fetal health.Keywords: cervical cancer, pregnancy, cancer in pregnancy, neoadjuvant chemotherapy